The regional impact of tourism when data is scarce : An application to the province of Salta - Romero, Carlos Adrián (2019)
Availability of updated and detailed official statistics at subnational level can sometimes be challenging, particularly in the developing world. This kind of data problems can become discouraging to governments trying to understand how their policies impact the economy, life and ecology of small regional areas. We use the case of the province of Salta, in Argentina, to show how, regardless of bad data problems, analysis of policy can be carried on successfully. Based on survey data and location quotients methodology we build a social accounting matrix for Salta. This estimated matrix allows use an input-output analysis to understand the relevance of tourism promotion programmes in the region.